ARTISTIC EXAMINATION OF TRADITIONAL PESHKIR SAMPLES REGISTERED IN A.R. İZZET KOYUNOĞLU MUSEUM - PALA YAVUZYİĞİT, Zehra (SSD Journal, 2022)
Handicrafts have always existed from the earliest times of humanity. Handicraft is an extensive area that includes several techniques, types, materials, and products. Especially Anatolia is a rich geography of art where the weaving culture is intensive and there is a high demand for handicraft products. The peshkirs (Towels), which contain very beautiful examples of handicraft products, appeared especially after the 18th century. In this study, 16 peshkir crafts in A.R. Izzet Koyunoğlu Museum were examined. In this direction, the official permissions required from the museum were taken, and the inventory records were searched. These crafts were discussed according to their technical, material, color, motif, and composition features. The common and different features of the peshkirs are referred to. In general, we see that there are samples where stylized flower and plant motifs are used in the patterns of the towel, and the weaving is self-patterned. It is determined that there are motifs in the herbal, geometric, figured, and symbolic groups.The samples examined were also grouped in accordance with embroidery techniques. It has been observed that techniques such as calculation craft, chinese needle, rolling with thread breaking, and bartın craft are used in embroidery. Obtained data are shown in tables.